The ameliorative effect of selenium on Azolla caroliniana grown under UV-B stress - Mostafa, E.M.; Hassan, A.M.A. (Phytoprotection, 2015)
Exposure of Azolla plants to UV-B radiation for 6 h resulted in a decrease in biomass and relative growth rate (RGR), which coincided with an increase in doubling time (DT) as compared with the control. Also, the protein content decreased. On the other hand, hydrogen peroxyde (H2O2) and malondialdehyde (MDA) accumulated significantly in UV-treated Azolla plants. Conversely, the addition of selenium (Se) at 1 ppm resulted in a significant increase in biomass and protein content of untreated and UV-treated Azolla plants, and a significant reduction in both H2O2 and MDA. Moreover, the addition of Se to UV-treated and untreated Azolla plants resulted in a significant increase in total ascorbate and total glutathione (GSH) contents compared with the control and UV-stressed Azolla plants. Also, glutathione redox potential (GSH/TG) increased significantly in UV-treated Azolla plants in the presence of Se. There also was a significant increase (38%) in ascorbate peroxidase (APX) activity in UV-treated plants compared with the control. APX activity in the presence of Se did not change significantly compared with the control. Glutathione reductase (GR) activity increased significantly in UV-treated Azolla, while glutathione peroxidase (GSH-PX) activity did not. On the other hand, both GSH-PX and GR activity in untreated and UV-treated Azolla plants were significantly enhanced by the application of Se to the nutrient media at a concentration of 1 ppm. Therefore, we can conclude that Se protects Azolla plants from UV-B stress.